STABILIZATION OF TEMPERATURE REGIMES WHILE SYNTHESIZING DIAMOND POWDERS - A. I. Dudiak; V. S. Yudenkov; V. M. Khvasko (Наука и техника)
The paper considers peculiar features of artificial diamond powder synthesis process and also direct and indirect methods for temperature measurement in a reaction cell of high-pressure apparatus. Differences in temperature regimes of diamond synthesis associated with time fixation of strain and heating power have been analyzed in the paper. The paper  reveals their impracticability.Theoretical methodology for temperature correction in the reaction cell has been proposed in the paper. An algorithm controlling cell material heating has been developed on the basis of a microcontroller and it makes it possible to stabilize temperature in the reaction mixture that permits to improve quality and strength characteristics of the obtained diamond powders. The paper contains a graphic interpretation of calculation results with the help of the proposed algorithm.